Government Incentives in the Development and Internationalization of the Real Sector in Turkey: A Theoretical Introduction - Yusufi, Ferimah (Journal of Applied And Theoretical Social Sciences, 2021)
In Turkey, the development and internationalization of the real sector are expressed as complementary industrialization strategies defining inward-oriented industrialization as “import substitution” and outward-oriented industrialization as “export-based industrialization”. Inward-oriented industrialization period can be conceptually considered the period in which the industrialization process is realized towards the domestic market; the export led industrialism process, on the other hand, can be considered the period in which the industrialization process takes place by integrating into the total circulation of the world industry and markets. The inward-oriented (domestic market) industrialization period should not be considered a period in which it was isolated from international power and industrialization dynamics, on the contrary, it should be taken into account that this period is shaped by the effects of international real sector, especially in Turkey. On the other hand, although the sectors which are effective in import substitution are in different forms, the outward-oriented industrialization process is basically the period in which the development and transformation of the same actors and sectors with financial, commercial, and industrial equipment has been observed since the establishment of the Republic. Although it is considered that both periods contain different policies along with the outward move since the beginning of this process which is the inward-oriented industrialization process, the process corresponds to different phases of industrialization as a whole. For this reason, government incentives in the formation and internationalization processes of the real sector have also altered and transformed.